2007
DOI: 10.1007/s11104-007-9256-y
|View full text |Cite
|
Sign up to set email alerts
|

Germination and seedling establishment of two annual grasses on lichen-dominated biological soil crusts

Abstract: Biological soil crusts dominated by lichens are common components of shrub-steppe ecosystems in northwestern US. We conducted growth chamber experiments to investigate the effects of these crusts on seed germination and initial seedling establishment of two annual grasses; the highly invasive exotic Bromus tectorum L. and the native Vulpia microstachys Nutt. We recorded germination time courses on bare soil and two types of biological soil crusts; one composed predominantly of the lichen Diploschistes muscorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
131
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 61 publications
11
131
0
1
Order By: Relevance
“…To clarify the relevance and role of all these aspects and to unravel the effect of temperature and watering frequency, more experiments using different methods can be performed employing, for example, growth chambers (e.g. Deines et al, 2007;De Frenne et al, 2012). In addition, A. pseudoplatanus also showed provenance-specific responses to increases in temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the relevance and role of all these aspects and to unravel the effect of temperature and watering frequency, more experiments using different methods can be performed employing, for example, growth chambers (e.g. Deines et al, 2007;De Frenne et al, 2012). In addition, A. pseudoplatanus also showed provenance-specific responses to increases in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…We analyze the impacts of warming and changes in precipitation frequency (as simulated by various watering intervals) on germination and early establishment of these two Acer species from different European provenances. A variety of techniques are available to study the effects of climate change on plant species including soil heating cables, open top chambers, growth chambers, and natural climatic gradients such as those across latitudes or elevations (Carón et al, 2015;De Frenne et al, 2013;Deines et al, 2007;Dunnett and Grime, 1999). The technique selected in each case depends on several factors including the life cycle phase that is being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the effects of microtopography, and water and nutrients fl uxes, BSC affect the distribution of resources in the soil, contributing to vegetation cluster patterns MARISELA PANDO-MORENO ET AL. (Deines et al, 2007) and probably improve water infi ltration and retention in the soil (Casenave and Valentin, 1989;Montaña et al, 1995;Rosentreter and Belnap, 2001;ReyesGómez et al, 2007;Yair, 2008;Chamizo et al, 2010).…”
mentioning
confidence: 99%
“…Studies have shown BSC having either facilitative, inhibitory or no effect on vascular plant establishment and cover (During and Van Tooren, 1990;Belnap et al, 2001). Existing evidence suggests that the effects of crusts on seed germination vary depending on the soil crust composition and plant characteristics (Lesica and Shelly, 1992;Zaady et al, 1997;Prasse and Bornkamm, 2000;Rivera-Aguilar et al, 2005;Serpe et al, 2006;Deines et al, 2007), as seeds vary in their germination requirements and consequently may respond differently to the conditions created by the crust (Baskin and Baskin, 1998). Positive effects of the crust on vascular plants may be the result of improved soil moisture conditions and nutrient availability, as well as a decrease in predation (During and Van Tooren, 1990;Belnap and Harper, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation